2018
DOI: 10.1007/s00701-018-3503-2
|View full text |Cite
|
Sign up to set email alerts
|

Upfront Gamma Knife surgery for facial nerve schwannomas: retrospective case series analysis and systematic review

Abstract: In our experience, RS and particularly GKS, using standard, yet low doses of radiation, appear to be a safe and effective therapeutic option in the management of these rare tumors. The results as from our systematic review are also encouraging with satisfactory rates of clinical stabilization and/or improvement and high rate of tumor control. Complications are infrequent and mostly transient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Large tumors can be treated using subtotal or gross total resection followed by GKR, as previously published in non-vestibular [8,29,49] and vestibular schwannomas [8,46]. Other approaches might include staged volume radiosurgery, in selected cases [7]. Challenging aspects might be related to the proximity with the optic apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large tumors can be treated using subtotal or gross total resection followed by GKR, as previously published in non-vestibular [8,29,49] and vestibular schwannomas [8,46]. Other approaches might include staged volume radiosurgery, in selected cases [7]. Challenging aspects might be related to the proximity with the optic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery (SRS) is considered a valuable therapeutic alternative for treating benign intracranial tumors, due to its minimal invasiveness as well as to its safety profile and efficacy on vestibular [14,24,34,44,45] and nonvestibular schwannomas [7,29]. Twenty years ago, a first report by Huang et al [16] evaluated the role of SRS by Gamma Knife (GK) in trigeminal nerve schwannomas.…”
Section: Introductionmentioning
confidence: 99%
“…44 Candidly, given that most studies of SRS reported essentially a zero incidence of degraded facial function, the differences observed in outcome may be predominantly driven by unfavorable outcomes following surgery, rather than favorable outcomes following SRS. 5,6,38,40 We did not identify a statistically significant difference in the incidence of complications, which ranged from 4% to 7%, or risk of progression, which ranged from 2% to 3% across all included studies, although the certainty of these findings is low. With respect to complications, we do note that, looking more broadly at the literature comparing out-comes after SRS and surgery, treatment-related morbidity and complications are almost universally lower following radiosurgery.…”
Section: Discussionmentioning
confidence: 68%
“…Screening against all selection criteria yielded 74 candidate studies, which underwent full-text analysis. Overall, 33 surgical 1,4, and radiosurgical 1,[5][6][7]19,[38][39][40][41][42] studies satisfied inclusion criteria into this study.…”
Section: Search Strategymentioning
confidence: 99%
“…PubMed (Comps et al, 2018) Upfront gamma knife surgery for facial nerve schwannomas: retrospective case series analysis and systematic review.…”
mentioning
confidence: 99%